Palliative care needs and experiences of patients with advanced heart failure and family caregivers in Asia: A mixed methods systematic review - Jingjing Li; Ping Guo; Hao Liu; Nikolaos Efstathiou (Palliative Medicine, 2026)
Background: The high prevalence of heart failure in Asia highlights the growing need for palliative care. However, access to palliative care remains limited. Understanding the palliative care needs and experiences of patients with heart failure and families is essential to inform policy and service development in diverse Asian contexts. Aims: To identify, appraise and synthesise recent evidence on palliative care needs and experiences of patients with advanced heart failure and family caregivers in Asia. Design: Mixed methods systematic review using a convergent integrated approach with thematic synthesis. The review protocol was registered with PROSPERO (CRD42024550688). Data sources: Eleven databases were searched for papers published between January 2010 and May 2024. Empirical studies on palliative care needs and experiences of patients with advanced heart failure and family caregivers were included and appraised using the Mixed Methods Appraisal Tool. Results: Twenty-nine papers (8 qualitative and 21 quantitative) were included. Three themes were identified: (1) Living a fragmented life with advanced heart failure: Patients experienced multidimensional suffering, loss of social connection and autonomy; (2) Planning for end of life: Multiple attitudes towards death, limited discussions, and diverse preferences made end-of-life care complex; and (3) Barriers and facilitators to palliative care delivery: Family dynamics, healthcare professionals’ perspectives and systemic factors shaped the accessibility and quality of palliative care. Conclusion: Cultural values enhance responsibility in family caregiving but limit patients’ involvement in end-of-life planning. Although palliative care needs are similar among Asian countries, they face diverse challenges in achieving equitable services. Strengthening providers’ skills, policy support, and culturally sensitive care models is essential.